MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SDN 11 KAMPUNG SURIAN KOTA SAWAHLUNTO - Adies Hikmy (Adaara: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims, to describe the plan of the principal in improving teacher performance at SDN 11 Kampung Surian, to describe the organization of principals in improving teacher performance at SDN 11 Kampung Surian, to describe the implementation of the principal in improving teacher performance at SDN 11 Kampung Surian, and to describe the principal's supervision in improving teacher performance at SDN 11 Kampung Surian. The research method is qualitative research using the case study method. Research informants as many as 6 people. The data collection tool was the researcher as the key instrument and the supporting instruments were interview guides, observation guides, field notes, and hand phones. Data collection techniques are participatory observation, in-depth interviews and documentation studies. The data analysis technique uses the Miles and Huberman model which divides the data analysis into three, namely data reduction, data presentation, and drawing conclusions. Data validity testing techniques use data triangulation and method triangulation. The results showed that starting from planning, organizing, implementing and supervising the principal's program in improving teacher performance, for example increasing discipline, providing motivation, conducting teacher training, supervising teacher performance, coaching teacher performance.